2006
DOI: 10.1021/jm0600904
|View full text |Cite
|
Sign up to set email alerts
|

Potent Benzimidazole Sulfonamide Protein Tyrosine Phosphatase 1B Inhibitors Containing the Heterocyclic (S)-Isothiazolidinone Phosphotyrosine Mimetic

Abstract: Potent nonpeptidic benzimidazole sulfonamide inhibitors of protein tyrosine phosphatase 1B (PTP1B) were derived from the optimization of a tripeptide containing the novel (S)-isothiazolidinone ((S)-IZD) phosphotyrosine (pTyr) mimetic. An X-ray cocrystal structure of inhibitor 46/PTP1B at 1.8 A resolution demonstrated that the benzimidazole sulfonamides form a bidentate H bond to Asp48 as designed, although the aryl group of the sulfonamide unexpectedly interacts intramolecularly in a pi-stacking manner with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…Among them, compound VII displayed high inhibition potency, with an IC 50 of 35 nM. It also exhibited significant cellular activity, increasing the insulin receptor phosphorylation level at 80 μM [53]. Collectively, these results illustrate that it is highly feasible to obtain potent and selective PTP1B inhibitors.…”
Section: Ptp1bmentioning
confidence: 76%
“…Among them, compound VII displayed high inhibition potency, with an IC 50 of 35 nM. It also exhibited significant cellular activity, increasing the insulin receptor phosphorylation level at 80 μM [53]. Collectively, these results illustrate that it is highly feasible to obtain potent and selective PTP1B inhibitors.…”
Section: Ptp1bmentioning
confidence: 76%
“…A related approach employed an isothiazolidinone (IZD)-based phosphoryl mimetic, which had previously been shown to be a superior for this use against PTP1B [82][83][84][85][86]. In the aforementioned study, a 3-formylphenyl group was introduced at the 5-position of the IZD ring to give intermediate 20 and then this was reacted with excess 1,3-diaminooxypropane to give the monomeric adduct 21 Fig.…”
Section: Oxime-based Click Chemistrymentioning
confidence: 99%
“…This group has gone on to incorporate the (S)-IZD pTyr mimetic into more druglike molecules and have demonstrated that benzimidazole sulfonamide containing (S)-IZD PTP1B inhibitors (Fig. 4B) can potently inhibit the enzyme, have cell permeability, and increase insulin signaling [Combs et al, 2006].…”
Section: Ptp1b Inhibitors For Metabolic Diseasesmentioning
confidence: 99%